Relationships between physiological characteristics and match demands in elite-level male field hockey players - Lombard, W. P.; Cai, X.; Lambert, M. I.; Chen, X.; Mao, L. (International Journal of Sports Science & Coaching, 2021)
This study investigated the physical characteristics, match demands and their relationships in elite-level male field hockey players (n = 23; 24 ± 3 years). Testing data were collected to investigate the physiological profiles of the players, while match demands were quantified with GPS data over 26 matches. There were significant differences (p = <0.05) between positional groups for pull ups, relative and absolute lower body strength, and body composition. Average total match distance for all the players was (5420 ± 1518 m). There were significant differences between positional groups for defenders (5770 ± 1419 m) vs strikers (4739 ± 1409 m) and midfielders (5549 ± 1545 m) vs strikers. The most high-speed-running (>4.5 ms-1) distance was covered by midfielders (950 ± 275 m) and strikers (908 ± 284 m). Midfielders (116 ± 15 m min) and strikers (120 ± 20 m min) achieved higher intensities during matches compared to defenders (105 ± 13 m min). There were small differences between positional groups for physiological variables, but large variation between positional groups for match demands. There was a significant negative relationship between 2.4 km time trial vs high-speed running (p = <0.05), player load.min and match speed (p = <0.001). Also, there was a negative association between repeat sprint ability total time and high-speed running distance (p = <0.02) and match speed (p = <0.02). The countermovement jump height was associated with match speed (p = <0.05) and there was a negative relationship between body fat % and match speed (p = <0.02). When considering key performance indicators while using GPS devices, match speed (m.min) provides the most valuable information in field hockey players.